Secrets of the killing state: the untold story of lethal injection - Lain, Corinna (New York University Press, 2025)
"Lethal injection is nothing like what you think. These are the Secrets of the Killing State. This is its untold story-a story of incompetence, law-breaking, lies and malfeasance, all covered by a heavy layer of secrecy"--